Effect of Lactobacillus in Broiler Chicken Fed Diets Enriched with Ï‰-3 Fatty Acids - Aparna, N; Karunakaran, R.; Parthiban, M.; Rao, V. Appa; Radhakrishnan, L. (Indian Journal of Animal Nutrition, 2022)
A research was conducted to study the effect of Lactobacillus supplementation in broiler chicken fed diet enriched with Ï‰-3 fatty acids. Two species of Lactobacilli were isolated from chicken gut and identified by in vitro sugar fermentation tests and by the gene sequencing of 16S RNA-23S RNA inter spacer region. The acid tolerance, bile tolerance and antioxidant activity test were done to determine the maximum probiotic potency by using probiotic score. L. salivarius with probiotic score of 170.94 compared to L. agilis with score of 129.14 was chosen for the feeding trial in broiler chicken. The freeze-dried L. salivarius exhibited 50% viability post freezing. Â In the feeding trial, the effect of L. salivarius at different level of supplementation viz., T1-without L. salivarius supplementation, T2- supplemented with L. salivarius at 106cfu/kg, T3- supplemented with L. salivarius at 109cfu/kg and T4- supplemented with L. salivarius at 1012cfu/kg in broiler chicken fed diet enriched with Ï‰-3 fatty acid was studied. Group T4 showed significant (P< 0.05) increase in weight gain and improvement in feed conversion ratio (FCR). There was no significant (P >0.05) difference in the meat quality parameters among treatments. The T1 showed significantly (P0.05) increase in linoleic acid, eicosa-pentaenoic acid (EPA), docosahexaenoic acid (DHA) and Ï‰- 6 fatty acids among the treatments. But the T4 showed numerical increase in EPA level (1.52 g/100 g total FA). It is concluded that T4 with dietary Ï‰-3 to Ï‰-6 fatty acid ratio of 1:3 and L. salivarius inclusion of 1012cfu/kg feed had produced broiler meat with Ï‰-3 to Ï‰-6 fatty acid ratio of 1:2.17 and EPA level of 1.52 g/100 g Total FA.